Pengaruh Kompensasi, Motivasi, Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada DPU Dan ESDM Kabupaten Boyolali - Pratiwi, Dita; , Drs. Suyatmin Waskito Adi, M.Si (2016)
This research was aimed to identify the influence of compensation, motivation and organization commitment to employee performance.This research population was entire employees on Duty Public Work and Energi of Mineral Resource Boyolali Regency. Sampel obtained counted 43 employees taken with purposive sampling tehnique. The data collecting method was using questionnaire. The data technique analyse was using the multippled linier regression analyze.Hypothesis test result shows that compensation, motivation and organization commitment has significant influence on employee performance (p value < 0,05). Determination coefficient value get obtained 0,435 this means that 43,5% employee performance could be influence compensation, motivation and organization commitment, while the rest equal to 56,5% can be explained the other variable outside in this research.